Pengaruh Aplikasi Solitekids Terhadap Minat Belajar Pada Anak 5-6 Tahun - Gusmaini Gusmaini; Susi Herlinda; Swandra Rahayu (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to determine the effect of the Solitekids application on learning interest in 5-6 year old children at Dahlia Kindergarten, Mempura District, Siak Regency. This research method is quasi-experimental, with a sample of 15 children in the experimental class and 16 in the control class. Data were collected through observation and documentation and analyzed using a t-test. The results of the study indicate that the use of Solitekids has a significant impact on learning interest, which is proven statistically, the independent sample t-test shows a Sig. (2-tailed) value of 0.000 <0.05, so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, the Solitekids application has been proven effective in increasing interest in learning in early childhood. Its contribution to teachers can be applied as a learning medium to increase children's interest in learning.